PENDIDIKAN BELA NEGARA SEBAGAI TONGGAK PERADABAN JIWA PATRIOTISME GENERASI MUDA - Rahmat Wijayanto J.; Marzuki Marzuki (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2018)
The purpose of this study was to provide an overview of state defense education carried out in Titian Teras H. Abdurrahman Sayoeti Jambi Senior High School through civic education and special curriculum. State defense education that is implemented in the school is carried out to shape the spirit and spirit of patriotime of students or young people in the face of the times and globaliza- tion. This study uses a qualitative approach. Data was obtained through interviews, and observa- tions of teachers and students from Titian Teras H. Abdurrahaman Sayoeti Jambi Senior High School. The results showed that the state defense education implemented in Titian Teras H. Abdurrahman Sayoeti Jambi Senior High School had a function in growing and strengthening the values of patrotism in students. Education defends the country teaches about love for the homeland, the spirit of struggle, nationalism, patriotism and excellent physical endurance. The material provided in- cludes insight into nationalism, line marching, time discipline, long march and leadership. Thus education in defense of the state has a positive contribution in shaping students who have a spirit of patriotism from an early age.